Functional analysis of recombinant 2‐Cys peroxiredoxin from the hard tick Haemaphysalis longicornis. Issue 1 (16th October 2015) - Kusakisako, K.; Masatani, T.; Miyata, T.; Galay, R. L.; Maeda, H.; Talactac, M. R.; Tsuji, N.; Mochizuki, M.; Fujisaki, K.; Tanaka, T.
Abstract: Ticks are obligate haematophagous arthropods that feed on vertebrate blood containing high levels of iron. The host‐derived iron reacts to oxygen in the tick's body, and then high levels of reactive oxygen species, including hydrogen peroxide (H2 O2 ), may be generated. High levels of H2 O2 cause oxidative stress to aerobic organisms. Therefore, antioxidant responses are necessary to control H2 O2 . We focused on peroxiredoxins (Prxs), H2 O2 ‐scavenging enzymes. The sequence of Haemaphysalis longicornis 2‐Cys Prx ( HlPrx2 ) was identified from fat body cDNA libraries of this tick and recombinant HlPrx2 was then prepared using Escherichia coli . By comparison with the 2‐Cys Prxs of other organisms, we found two conserved cysteines in HlPrx2, Cys51 and Cys172. We examined the antioxidant activity of HlPrx2 and mutant proteins produced by a single base substitution, converting one or both of these cysteines into serines. The assays revealed that proteins containing Cys51 showed antioxidant activity when H2 O2 was removed. Sodium dodecyl sulphate polyacrylamide gel electrophoresis and size‐exclusion chromatography demonstrated that only the wild‐type HlPrx2 formed homodimers and that all of the proteins that we made had a high molecular weight peak. These results indicate that both Cys51 and Cys172 are essential for the dimerization of HlPrx2, whereas only the Cys51 residue is necessary for antioxidant activity.